Cardiac registers: the adult cardiac surgery register. Issue 18 (29th May 2010) - Bridgewater, Ben; ,
Abstract : Aims of the scts adult cardiac surgery database: To measure the quality of care of adult cardiac surgery in GB and Ireland and provide information for quality improvement and research. Quality of care interventions: Feedback of structured data to hospitals, publication of named hospital and surgeon mortality data, publication of benchmarked activity and risk adjusted clinical outcomes through intermittent comprehensive database reports, annual screening of all hospital and individual surgeon risk adjusted mortality rates by the professional society. Setting: All NHS hospitals in England, Scotland and Wales with input from some private providers and hospitals in Ireland. Years: 1994-ongoing. Population: Consecutive patients, unconsented. Current number of records: 400000. Startpoints: Adult cardiac surgery operations excluding cardiac transplantation and ventricular assist devices. Baseline data: 129 fields covering demographic factors, pre-operative risk factors, operative details and post-operative in-hospital outcomes. Data capture: Entry onto local software systems by direct key board entry or subsequent transcription from paper records, with subsequent electronic upload to the central cardiac audit database. Non-financial incentives at hospital level. Data quality: Local validation processes exist in the hospitals. There is currently no external data validation process. Endpoints and linkages to other data: All cause mortality is obtained through linkage with Office for National Statistics. No other linkages exist at present. Access to data: Available for research and audit by application to the SCTS database committee at http://www.scts.org .